Is Tourism Coordinated with the Economy and the Environment in Natural World Heritage Cities in China? - Xiangju Zhang; Zhixuan Huang; Yongsheng Li; Ximei Li (Land)
For tourist cities, coordination between tourism and socio-economic and natural environments is crucial for sustainable urban development. While the positive correlation between a Natural World Heritage (NWH) designation and local urban tourism growth has been validated, the interplay among tourism, the economy, and the environment remains underexplored. We conceptualize NWH cities as complex adaptive systems and establish an evaluation framework to assess the relationships among tourism, economic, and environmental subsystems. Using 34 NWH cities in China as case studies, we apply a coupling coordination degree model to evaluate the sustainability indices of the three subsystems and their interrelationships. Additionally, the obstacle degree model identifies specific obstacles in cities with suboptimal coordination, leading to targeted management recommendations. Our findings reveal that while tourism and economic sustainability indices have shown consistent upward trends, environmental sustainability has experienced a decline. The coupling coordination degrees among the three subsystems have generally increased, albeit with fluctuations in some cities. Environmental-related indicators are the main obstacle factors to imbalanced development in some cities from 2015 to 2020. Therefore, the primary challenge for sustainable management lies in the environmental subsystem. This study provides a relational perspective for evaluating the sustainability of NWH cities and offers targeted recommendations for enhancing their sustainable development, contributing to the broader discourse on heritage management and sustainable urban practices.